Summer Abundance and Distribution of Proteorhodopsin Genes in the Western Arctic Ocean - Boeuf, Dominique; Lami, Raphaël; Cunnington, Emelyne; Jeanthon, Christian (Frontiers in Microbiology, 2016)
Proteorhodopsins (PR) are phylogenetically diverse and highly expressed proton pumps in marine bacterial communities. The phylogenetic diversity and in situ expression of the main PR groups in polar off-shore, coastal and estuarine waters is poorly known and their abundance has not yet been reported. Here, we show that PR gene sequences of the southern Beaufort Sea including MacKenzie shelf and estuary are mainly affiliated to Gammaproteobacteria, Alphaproteobacteria and Bacteroidetes. Substantial overlap (78%) between DNA- and cDNA-based librairies indicated in situ PR transcription within a large fraction of PR-containing community. Sets of specific qPCR primers were designed to measure the absolute abundances of the major PR types. Spatial and depth profiles showed that PR-containing bacteria were abundant throughout the photic zone, comprising up to 45% of total bacteria. Although their abundance varied greatly with location and depth, Alphaproteobacteria predominated in the PR community in all water masses, with SAR11 as the major PR type. Low nutrient concentrations rather than light were the environmental drivers that best explained the abundance and distribution of arctic PR types. Together, our data suggests that PR-based phototrophy could be the major phototrophic prokaryotic process during the Arctic Ocean summer.